2010
DOI: 10.1213/ane.0b013e3181c76f70
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nabilone on Sleep in Fibromyalgia: Results of a Randomized Controlled Trial

Abstract: Nabilone is effective in improving sleep in patients with FM and is well tolerated. Low-dose nabilone given once daily at bedtime may be considered as an alternative to amitriptyline. Longer trials are needed to determine the duration of effect and to characterize long-term safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
185
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 242 publications
(194 citation statements)
references
References 27 publications
1
185
0
8
Order By: Relevance
“…Although adverse events in the active treatment group were not serious, they were common (77). In studies examining the endocannabinoid-based drug "Nabilone" on pain outcomes in fibromyalgia, the statistically significant effects were outweighed when side effects were taken into consideration (78)(79)(80). In a separate review of cannabinoid-based therapies in chronic pain conditions, three of which were rheumatic pain (2 fibromyalgia, 1 RA), concluded that while the majority demonstrated improvements in pain, no direct evidence on effects of herbal marijuana in rheumatic pain (78).…”
Section: Current Work and Future Direction Of Researchmentioning
confidence: 99%
“…Although adverse events in the active treatment group were not serious, they were common (77). In studies examining the endocannabinoid-based drug "Nabilone" on pain outcomes in fibromyalgia, the statistically significant effects were outweighed when side effects were taken into consideration (78)(79)(80). In a separate review of cannabinoid-based therapies in chronic pain conditions, three of which were rheumatic pain (2 fibromyalgia, 1 RA), concluded that while the majority demonstrated improvements in pain, no direct evidence on effects of herbal marijuana in rheumatic pain (78).…”
Section: Current Work and Future Direction Of Researchmentioning
confidence: 99%
“…Sentetik bir tetrahidrokanabinol türevi olan Nabilon fibromiyalji tedavisinde iki çalışma ile değerlendirilmiştir. Hastaların yaklaşık 2 hafta takip edildiği çalışmada nabilonun amitriptiline göre uyku problemlerinde daha etkili olduğu, ağrı ve yaşam kalitesi üzerine ise üstünlüğü olmadığı gösterilirken; ikinci çalışmada plasebo ile karşılaştırıldığında ağrı ve yaşam kalitesinde anlamlı düzelme sağlamıştır 81,82 . Sık görülen yan etkileri arasında baş dönmesi, sersemlik ve bulantı sayılabilir.…”
Section: Kannabioidlerunclassified
“…Therefore, cannabinoids may have a major role for patients who suffer sleep disturbance because of chronic pain or other chronic illness [8]. Ware et al [25] showed the benefit of nabilone in helping sleep in fibromyalgia.…”
Section: Other Emerging Uses In Neurological Diseasementioning
confidence: 99%